2016
DOI: 10.1002/anie.201607276
|View full text |Cite
|
Sign up to set email alerts
|

UV‐Induced Disulfide Formation and Reduction for Dynamic Photopatterning

Abstract: Here we present the UV-induced disulfide formation (UV-DF) and disulfide reduction (UV-DRSpatially resolved functionalization of surfaces is important in a variety of research fields ranging from microfluidics [1] and electronics [2] to biotechnology. [3] In this context, photochemical reactions attracted attention, because they offer both spatial and temporal control of surface modification. [4] To date, a variety of light-triggered reactions, for example, thiol-ene [5] /yne, [6] photoinitiated azide-yne, [7]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 33 publications
0
24
0
2
Order By: Relevance
“…Alternatively, photodynamic patterning also allows for spatiotemporal control of wettability at surfaces, as demonstrated previously for disulfide formation/reduction strategies ( Figure A) . The modularity of the disulfide bond provides the opportunity to attach, exchange and detach different thiol components at a thiol‐modified surface without a significant loss of functionality over time.…”
Section: Responsive Wettabilitymentioning
confidence: 91%
“…Alternatively, photodynamic patterning also allows for spatiotemporal control of wettability at surfaces, as demonstrated previously for disulfide formation/reduction strategies ( Figure A) . The modularity of the disulfide bond provides the opportunity to attach, exchange and detach different thiol components at a thiol‐modified surface without a significant loss of functionality over time.…”
Section: Responsive Wettabilitymentioning
confidence: 91%
“…It was mentioned above that care should be taken during the photo(co)polymerization of disulfides containing cross‐linkers. Indeed, disulfides are sensitive to UV light and can undergo exchange reactions with other disulfide molecules, irrespective of the solvent conditions, which implies that light can be employed to degrade networks in the presence of soluble thiols and disulfides.…”
Section: Challenge: Adaptive Direct Laser Written Materialsmentioning
confidence: 99%
“…Numerous materials based on disulfide bond exchange can be found in the literature, and the relatively weak dynamic bond has been widely used for the design of healable or recyclable materials . A particularly attractive feature of the disulfide bond is its sensitivity to various stimuli such as heat, pH, or light, and a few examples of disulfide containing thermoresponsive adhesives have been reported . A photohealable semicrystalline shape‐memory polydisulfide network was investigated by Rowan and co‐workers, who demonstrated that such materials may also serve as reversible, on‐demand debondable adhesives ( Figure a) .…”
Section: On‐demand Debonding Based On Reversible Bondsmentioning
confidence: 99%